Development of a new readout system for HVCMOS sensors for the LHCb mighty tracker - Schmitz, Hannah; Dittmann, Lucas; Neubert, Sebastian; Padeken, Klaas Ole (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2024)
A new downstream tracking system, known as the Mighty Tracker, is planned to be installed at LHCb during LS4 of the LHC. This will allow an increase in instantaneous luminosity from 2⋅1033cm−2s−1 to 1.5⋅1034cm−2s−1 and therefore an overall higher irradiation and up to six times higher occupancy. To keep the material budget as low or even lower as for the current detector, the Mighty Tracker is planned as a hybrid system with silicon pixels in the inner and scintillating fibers in the outer region. For the pixel detector part HV-CMOS MAPS with a pixel size of 55×165μm2 will be used. This technology has been chosen because of its low production costs, low material budget, high radiation tolerance and good timing resolution. To characterize and further develop the MightyPix, a new readout system called MARS (Mighty TrAcker Readout System) has been developed. MARS is a modular system, able to test different single chips in the laboratory as well as at testbeam facilities. It has been used to perform first studies with development-chips investigating the system itself and its performance. Further, a first sensor characterization of the MightyPix started with another readout system — GECCO.